Impact of pre-existing treatment with statins on the course and outcome of tick-borne encephalitis - Bogovič, Petra (PLoS One, 2018)
OBJECTIVES: Although statins have anti-inflammatory and potentially also antimicrobial (including antiviral) activity, their therapeutic impact on infectious diseases is controversial. In this study, we evaluated whether pre-existing statin use influenced the course and outcome of tick-borne encephalitis. METHODS: To assess the influence of statin usage on the severity of acute illness and the outcome of tick-borne encephalitis, univariate and multivariable analyses were performed for 700 adult patients with tick-borne encephalitis of whom 77 (11%) were being treated with statins, and for 410 patients of whom 53 (13%) were receiving statins, respectively. RESULTS: Multivariable analyses found no statistically significant association between statin usage and having a milder acute illness. There was also no statistically significant benefit with respect to a favorable outcome defined by the absence of post-encephalitic syndrome (ORs for a favorable outcome at 6 months was 0.96, 95% CI: 0.46–2.04, P = 0.926; at 12 months 0.29, 95% CI: 0.06–1.33, P = 0.111; at 2–7 years after acute illness 0.44, 95% CI: 0.09–2.22, P = 0.321), by a reduction in the frequency of six nonspecific symptoms (fatigue, myalgia/arthralgia memory disturbances, headache, concentration disturbances, irritability) occurring during the 4 week period before the last examination, or by higher SF-36 scores in any of the eight separate domains of health as well as in the physical and mental global overall component. Furthermore, there were no significant differences between patients receiving statins and those who were not in the cerebrospinal fluid or serum levels for any of the 24 cytokines/chemokines measured. CONCLUSIONS: In this observational study, we could not prove that pre-existing use of statins affected either the severity of the acute illness or the long-term outcome of tick-borne encephalitis.